Distributed embedded Smart Cameras : architectures, design and applications - Velipasalar, Senem; Bobda, Christophe (Springer New York, 2014)
This publication addresses distributed embedded smart cameras -cameras that perform onboard analysis and collaborate with other cameras. This book provides the material required to better understand the architectural design challenges of embedded smart camera systems, the hardware/software ecosystem, the design approach for, and applications of distributed smart cameras together with the state-of-the-art algorithms. The authors concentrate on the architecture, hardware/software design, realization of smart camera networks from applications to architectures, in particular in the embedded and mobile domains. •                    Examines energy issues related to wireless communication such as decreasing energy consumption to increase battery-life •                    Discusses processing large volumes of video data on an embedded environment in real-time •                    Covers design of realistic applications of distributed and embedded smart cameras